'I wouldn't know what to do with the breasts': the impact of patient gender on medical student confidence and comfort in clinical skills. Issue 6 (2nd November 2022) - Politis, Marina; El Brown, Megan; Huser, Camille AM; Crawford, Lynsay; Pope, Lindsey
ABSTRACT: Background: Previous research has found a relationship between students' gender and attitudes surrounding peer physical examination, but relationship between patient gender and confidence/comfort is less clear. We explored whether patient gender affects medical students' levels of confidence and comfort in clinical examination skills. Methods: An electronic survey and focus groups were conducted with medical students from one UK institution. Students reported levels of confidence/comfort when carrying out clinical examinations on men/women. An inductive thematic analysis was performed. Results: Of a total of 1500 students provided with the opportunity to participate, ninety (6%) responded. For cardiovascular and respiratory examinations, confidence/comfort were higher when examining male-presenting patients. The opposite was true for mental state examinations. Barriers to confidence/comfort included perceiving males as a norm, difficulty navigating breasts, tutors' internalised gendered attitudes and a wider sociocultural issue. Facilitators of confidence/comfort included students relating to patients, embodying a professional role, gender blindness, and authentic clinical environments. Fewer than 20% (n = 18) of students felt they had enough opportunity to practice clinical skills on women, versus 90% (n = 82) on men. Conclusion: Our study identified an area where students' confidence and comfort in clinical examinations could be enhanced within medical education. Changes were implemented in the institution under study's vocational skills teaching, which is rooted in general practice. Information on gender and clinical skills was provided within course handbooks, time was scheduled to discuss gender and clinical skills in small group settings, and equitable gender representation was ensured in clinical assessment.